IMPLEMENTASI NILAI PANCASILA PADA GENERASI Z - Azzahra Shakila Meisa Putri; Resi Setiawati; Hendy Widodo (STKIP Al Islam Tunas Bangsa dan HEPI Korda Lampung, 2022)
The values ​​contained in Pancasila have never changed, what has changed is only those who apply the values ​​of Pancasila which have started to fade due to the times. Generation Z has experienced a decline in the values ​​of Pancasila, nationalism and patriotism in their souls because they follow the development of increasingly sophisticated science and technology, globalization and promiscuity. For this reason, it is necessary to implement Panacasila to change this behavior. In this study using qualitative analysis or methods, namely finding research methods or discussions obtained from many sources such as books, articles and research on the phenomenon and further research on the substance of the phenomenon. This research was made to foster the spirit of nationalism so that this generation is not indifferent to the values ​​contained in Pancasila. Therefore, the values ​​contained in Pancasila must continue to be implemented in everyday life.